Perceived Social Change, Parental Control, and Family Relations: A Comparison of Chinese Families in Hong Kong, Mainland China, and the United States - Fung, Joey; Kim, Joanna J.; Jin, Joel; Wu, Qiaobing; Fang, Chao; Lau, Anna S. (Frontiers in Psychology, 2017)
This study examined the relationship between perceived social change, parental control and family relations in a sample of 419 4th and 5th grade children and their mothers who are of Chinese descent but reside in three different contexts: Los Angeles (LA), Hong Kong (HK), and Beijing (BJ). HK mothers endorsed the highest levels of psychological control and the lowest levels of autonomy support compared to BJ and LA mothers. Perceived social change as measured by mothers’ endorsement of new values and ideologies was associated with increased use of both autonomy support and psychological control. Results of the mediation analyses suggested that perceived social change explained differences between LA and HK mothers in autonomy support, but group differences in psychological control were magnified when perceived social change was accounted for. Finally, whereas autonomy support was associated with higher levels of child perceived acceptance in HK and LA, psychological control was associated with greater family conflict in BJ and LA. Findings suggested that as families undergo urbanization or social change, it may shift the implications of traditional strategies that are intended to socialize the child towards interpersonal attunement. Overall, the study highlights the importance of moving beyond ethnic-group or cross-national comparisons to investigate the role of changing social and economic contexts in understanding differences in the use of parental control and their associations with family relations.